Time Course of the Effects of Buxin Yishen Decoction in Promoting Heart Function and Inhibiting the Progression of Renal Fibrosis in Myocardial Infarction Caused Type 2 Cardiorenal Syndrome Rats - Qiu, Qi; Cao, Jinglin; Wang, Yong; Zhang, Yunnan; Wei, Yun; Hao, Xiaoyan; Mu, Yu; Lin, Yang (Frontiers in Pharmacology, 2019)
This study aimed to investigate the therapeutic effect of traditional Chinese medicine-Buxin Yishen decoction (BXYS) on type 2 cardiorenal syndrome (CRS) caused by myocardial infarction and explore the possible mechanism BXYS works. A chronic heart failure (CHF) rat model induced by LAD ligation was used and five groups were created that included a sham group, a CHF model group, a fosinopril group, a BXYS (0.4 g/kg) group and a BXYS (0.8 g/kg) group. Heart function, renal hemodynamics, neuroendocrine factors, serum and urine concentration of soluble form connective tissue growth factor (sCTGF), expression of CTGF mRNA, CTGF, α-smooth muscle actin (α-SMA), and low-density lipoprotein receptor-related protein (LRP) in renal tissues were evaluated after 28 days and 60 days of drug administration. Histological analysis of kidney tissues was also performed. In vitro experiments were designed to verify the results of in vivo experiments by detecting factors including CTGF, α-SMA in NRK-52E cells. Rats with CHF showed obvious pathophysiological changes including: altered renal hemodynamic parameters; dysregulated heart function; changes to serum concentrations of angiotensin II (AngII), cyclic guanosine monophosphate (cGMP), serum creatinine (Scr), blood urea nitrogen (BUN), C-reactive protein (CRP), brain natriuretic peptide (BNP); high serum and urine sCTGF concentration; high CTGF mRNA, CTGF, α-SMA and LRP expression in renal tissues; increased extracellular matrix (ECM) deposition and fibrosis in renal tissues. Treatment of BXYS was correlated with a restoration of heart function and improvement of renal hemodynamics, lower serum and urine sCTGF, lower CTGF mRNA, CTGF, α-SMA and LRP expression in renal tissues and lower ECM deposition. In addition, in vitro experiments showed that treatment with BXYS reduced the α-SMA and LRP concentration in NRK-52E cells, which was similar in vivo experiments. In conclusion, the current study provided evidences that BXYS played a role in improving heart function and delaying the progress of renal fibrosis. Meanwhile, the CTGF-LRP pathway might be one of the therapeutic targets for myocardial infarction caused type 2 CRS which showed a positive change after BXYS treatment and is worthy of further exploration.